The Relationship Between Nurse Motivation And The Quality Of Care of Nursing Documentation In The Hospitas Dr. Bratanata - Maldanurman Putri, Rivi; Mawarti, Indah; Sulistiawan, Andika (Jurnal Keperawatan Universitas Jambi, 2024)
Nursing documentation is an important part of the nursing care process as proof of responsibility answered the nurse. Nursing documentation is used as an indicator in determining quality Nursing is also a basis for decision making. This research aims to find out research related to the relationship between nurse motivation and the quality of nursing care documentation in the hospital Dr.Bratanata jambi city. Methods The research method uses a correlational study using a cross-sectional approach. The sampling technique was carried out by total sampling technique, namely by sampling which was carried out by selecting samples that met the criteria. The results based on statistical analysis using the Spearman rank test of 53 samples obtained p value = 0.036 because p< 0.05, it is stated that there is a relationship between motivation and documentation of nursing care at Dr Bratanata Hospital. Results This research is based on research conducted is that there is a relationship between motivation and the quality of care documentation in hospitals Dr. Bratanata Jambi. So it is hoped that nurses will increase their knowledge capacity about maintenance documentation and improving performance in documenting maintenance because good documentation can improve hospital services and become a responsibility and good accountability.